Use it or lose it how we get to be who we are - Bortz, Walter; American College of Sports Medicine; Monterey Bay Video Production Co.; Insight Media ([Indianapolis, In.] : Monterey Bay Video Production Co. [production] ; New York : Insight Media [distributor], 2004)
Discusses the dilemma concerning how to get people to take advantage of the knowledge concerning the positive impact of exercise on the human body
Title from title screen
Keywords: Diet; Health